Response of Cotton to Drip and Surface Irrigation in Saline Vertisols - Rajak, Dateshwa; Manunatha, M V; Rajkumar, G R; Ravishankar, G (Journal of Agricultural Engineering, 2010)
A field experiment was conducted on saline vertisols at Gangavati, Karnataka to study the response of cotton (Gossypium hirsutum L.) to drip and surface irrigation at various irrigation water (IW) to ET ratios viz., 0.8 ET, 1.0 ET, 1.2 ET and 1.4 ET. Crop response in terms of plant height, number of branches and number of bolls per plant was better under drip as compared to surface irrigation. The highest cotton yield was recorded in drip irrigation at 1.2 ET (1.74 t/ha), followed by the same at 1.4 ET (1.65 t/ha), while the lowest was with surface irrigation at 0.8 ET (1.10 t/ha). The net saving in water through drip irrigation was 23.8, 18.1, 13.6 and 9.9 % at 0.8, 1.0, 1.2 and 1.4 ET, respectively as compared to the same levels of irrigation through surface method. The highest (22.9 kg.ha?¹.cm?¹) and lowest (13.5 kg.ha?¹.cm?¹) water production efficiencies were achieved in case of drip irrigation at 0.8 ET and surface irrigation at 1.4 ET, respectively. The highest (2.00) and lowest (1.23) gross benefit-cost ratios were achieved in surface irrigation with 1.2 ET and drip irrigation at 0.80 ET, respectively.